Comparative analysis of male germ cell proliferation and apoptosis in wild and captive Atlantic bluefin tuna (Thunnus thynnus L.). (14th August 2012) - Zupa, R.; Fauvel, C.; Mylonas, C. C.; Santamaria, N.; Valentini, L.; Pousis, C.; Papadaki, M.; Suquet, M.; de la Gándara, F.; Bello, G.; De Metrio, G.; Corriero, A.
Summary: The most commonly observed reproductive dysfunction in male fishes reared in captivity is reduction in sperm volume and quality. The Atlantic bluefin tuna Thunnus thynnus (Osteichthyes: Scombridae) is one of the few large pelagic and migratory marine fishes maintained in captivity with the purpose of establishing breeding populations to support an aquaculture industry. The objectives of the present study were to compare male germ cell proliferation and apoptosis between wild and captive individuals at two different phases of the spermatogenetic cycle, and to evaluate sperm motility characteristics of captive individuals. Histological observations were performed to analyze testicular activity, and germ cell proliferation and apoptosis were evaluated through the immunohistochemical detection of proliferating cell nuclear antigen (PCNA) and the terminal deoxynucleotidyl transferasemediated d'UTP nick end labeling (TUNEL) method, respectively. Computer‐assisted sperm analysis (CASA) was used to evaluate sperm motility. Results showed that germ cell proliferation was delayed and germ cell apoptosis increased in captive animals relative to wild individuals. Sperm motility of samples obtained from captive individuals was anomalous, both in terms of motility duration and swimming efficiency. Thus it appears that rearing in captivity impairs male reproductive function through, at least, changes in germ cell proliferation and apoptosis.